Garbage to fuel a feasibility study on the commercial scale production and distribution of CNG - Chung, Vincent Arnold; Gatpandan, Ana Carmela; Solano, Nina Patricia
This feasibility study was conducted to determine the viability of the production and distribution of compressed natural gas (CNG) as an alternative fuel source for the Philippine transport sector, using accelerated anaerobic garbage digesting method to answer the solid waste disposal and air pollution problems of the Philippines. The project's target market is the transport sector, aiming to tap the public transport sector in the first three years of operation, then the private transport sector on the fourth year of operation onwards. Based on the results of the demand, supply, industry, and competitor analyses, it was concluded that CNG from solid waste is a potentially effective solution to the country's environmental and economic problems because it can help solve problems on solid waste disposal and air pollution due to the garbage usage for its production and its lower emission results, and can bring about lower fuel costs and improved fuel consumption. Moreover, results from technical study, financial study, as well as social profitability study further strengthens the idea that commercial scale production and distribution of CNG is a commercially viable business that can bring about reasonable return on investment not only to the business owners but to the bus companies, private transport vehicle owner, and to the society as a whole.